Effects of sevuparin on rosette formation and cytoadherence of Plasmodium falciparum infected erythrocytes - Somporn Saiwaew (2018)
© 2017 Saiwaew et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. In severe falciparum malaria cytoadherence of parasitised red blood cells (PRBCs) to vascular endothelium (causing sequestration) and to uninfected red cells (causing rosette formation) contribute to microcirculatory flow obstruction in vital organs. Heparin can reverse the underlying ligand-receptor interactions, but may increase the bleeding risks. As a heparinderived polysaccharide, sevuparin has been designed to retain anti-adhesive properties, while the antithrombin-binding domains have been eliminated, substantially diminishing its anticoagulant activity. Sevuparin has been evaluated recently in patients with uncomplicated falciparum malaria, and is currently investigated in a clinical trial for sickle cell disease. The effects of sevuparin on rosette formation and cytoadherence of Plasmodium falciparum isolates from Thailand were investigated. Trophozoite stages of P. falciparum-infected RBCs (Pf-iRBCs) were cultured from 49 patients with malaria. Pf-iRBCs were treated with sevuparin at 37?C and assessed in rosetting and in cytoadhesion assays with human dermal microvascular endothelial cells (HDMECs) under static and flow conditions. The proportion of Pf-iRBCs forming rosettes ranged from 6.5% to 26.0% (median = 12.2%). Rosetting was dose dependently disrupted by sevuparin (50% disruption by 250 μg/mL). Overall 57% of P. falciparum isolates bound to HDMECs under static conditions; median (interquartile range) Pf-iRBC binding was 8.5 (3.0-38.0) Pf-iRBCs/1000 HDMECs. Sevuparin in concentrations ô 100 μg/mL inhibited cytoadherence. Sevuparin disrupts P. falciparum rosette formation in a dose dependent manner and inhibits cytoadherence to endothelial cells. The data support assessment of sevuparin as an adjunctive treatment to the standard therapy in severe falciparum malaria.